Comparative method in criminal law as a tool of legal research and education - Kamensky, Dmitriy; Vlasov, Andrii; Hrankina, Valentyna; Sharmar, Olha; Danylevska, Yuliia (DIXI, 2026)
The study explores the comparative method in criminal law as a crucial tool for legal research and education. The authors examine its application in different legal traditions, while pointing out significant differences between common law and continental law approaches. They argue that globalization has heightened the need for comparative legal studies, as nations increasingly interact and adapt legal principles across jurisdictions. However, the research highlights challenges, particularly the strong differences in criminal law systems, shaped by historical, cultural, and political factors. The paper employs key methodological tools, such as analysis, synthesis, and modeling, which help structure comparative legal research. It also emphasizes the role of comparative law in overall legal harmonization and reform, while providing insights into how legal systems define crimes, determine liability, and apply punishments. The authors conclude that comparative criminal law should not exist in isolation but as part of broader comparative legal studies, thereby contributing to the development of criminal law theory and practice. This research is particularly relevant in the context of Ukraine’s legal integration with European and other global legal systems, demonstrating how comparative methodology can inform national legal reforms and improve the effectiveness of criminal justice systems worldwide.